1,5-Phosphonium betaines from N-triflylpropiolamides, triphenylphosphane, and active methylene compounds - Fiore, Vito A.; Freisler, Chiara; Maas, Gerhard (Beilstein Journal of Organic Chemistry, 2019)
N-Phenyl-N-(trifluoromethylsulfonyl)propiolamides react with triphenylphosphane in the presence of various active methylene compounds CH2XY in a 1:1:1 molar ratio to furnish 1-phosphonium-5-oxabetaines, Ph3P+–C(R)=CH–C(O–)=CXY. These betaines are formed preferentially, but not exclusively, as E-diastereoisomers with respect to the vinylic double bond. In some cases, separation of the two diastereoisomers was achieved by fractionating crystallization. Structure determination by X-ray diffraction analysis revealed marked conformational differences around the CH–C(O–) single bond of E and Z-isomers and extended charge delocalization in the anionic part.
Keywords: betaines; multi-component reactions; N-triflylamides; phospha-Michael reaction; propiolamides